Problematika Desain Komunikasi Visual dan Plagiarisme dalam Dunia Desain Grafis - Royhan, Muhammad Ghoyyas; Ngabekti, Dhevin Kawistoro (ISI Press Institut Seni Indonesia Surakarta, 2021)
The development of technology, especially the internet, triggers graphic designers to be more active and creative in their work. Publication of graphic design works through social media and other media, but as a result of that plagiarism is also very rampant because of easy access to see other people's work via the internet. The formulation of the problem to get a solution through research is how to increase the creativity of the creators. Design of visual communication that is useful or beneficial for the general public and how to try to suppress plagiarism in graphic design. Qualitative Research Methods as an approach that focuses on data analysis and data solutions in understanding the social phenomena of graphic design creativity and design plagiarism that occur in society. there is also a way to just use other people's work as a source of inspiration and modify it as creatively as possible.